The Effect of CLT Method On Students' Speaking Skillat The Second Grade of MTSN 1 Kolaka - Zakaria Zakaria; Rani Royani (Institute for Research and Scientific Publications STKIP Singkawang, 2017)
This research presented about the effect of CLT Method on Students' Speaking Skill at the Second Grade of MTsN 1 Kolaka. The research question was "is there significant effect of CLT Method on Students' Speaking Skill at the Second Grade of MTsN 1 Kolaka?" The objective was to find out the effect of CLT method, the data and information about students' speaking skill at the second grade of MTsN 1 Kolaka. The design of this research was quasy expriment in two classes with pre-test and post-test design. The sample were class VIII MTsN 1 Kolaka of 208 students and took 54 students as the sample. The instruments were speaking test comprehension. Data collection techniques in this research were giving pre-test, treatment, and post-test. The result it was found that in expriment class the mean score of pre-test (52,2) was smaller than the mean score of post-test (62,6) it means that the increased of the students' speaking SKILL was 37% (0,51) and the value of was bigger than at the significant level 0,05 and degree of freedom -26, it means that   was rejected and  was accepted. It can concluded that there was an effect of CLT  method on students' speaking skill at the second grade of MTsN 1 Kolaka.